Bioactive compounds of palm kernel cake - Ahmad, Khairunisa Amira (2015)
In Malaysia, the incidence of cancer is increasing and it is ranked number four as a disease that caused death. One of the causes of cancer is the presence of free radicals especially reactive oxygen species (ROS). Antioxidants are able to scavenge free radicals and inhibit their formation. The research of finding antioxidants in natural products such as from plant has been increasing because the use of synthetic antioxidants may be toxic to humans. Plant contains secondary metabolites that are considered as bioactive compounds because they have pharmacological potentials which give benefits to human health. In this study, palm kernel cake (PKC) was used as a source of bioactive compounds for antioxidant and anticancer activities. The results showed that PKC extracts possessed antioxidant activity as the compounds present were able to scavenge 2,2-diphenyl-1-picryl-hydrazyl (DPPH) free radical. Extracts prepared from freeze-dried extract were better when compared to that prepared from oven dried PKC. The IC50 value obtained was 487±0.02 μg/ml. PKC extracts also showed anti-cancer property significantly (P < 0.05) when they were used to treat cancer cell lines in vitro, in a dose dependent manner. PKC extracts were able to reduce the cell viabilities of human breast cancer cell line (MCF-7), human hepatoma cancer cell line (HepG2), human lung cancer cell line (A549) and human cervical carcinoma cancer cell line (HeLa). The PKC extracts were observed to contain high phenolic compounds. For freeze-dried PKC extract, the total phenolic content was 15.26±1.18 mg GAE/g of PKC extract and 7.61±0.87 mg GAE/g for oven-dried PKC extract. Most of the compounds analysed by gas chromatography mass spectrometry (GCMS) were fatty acids and phenols and their derivatives. The phenolic compounds were known to have antioxidant and anticancer activities.